2020
DOI: 10.1111/ijfs.14632
|View full text |Cite
|
Sign up to set email alerts
|

Improved solubility of proteins from white and red clover – inhibition of redox enzymes

Abstract: New alternative protein sources are needed. Clover grasses as white clover (WC) and red clover (RC) may provide a novel protein source to achieve high-quality food protein. To prevent protein oxidation, endogenous oxidative enzymes as polyphenol oxidase (PPO) and peroxidases were inhibited with sulphite. RC showed higher PPO activity than WC. Low sulphite inhibited the PPO activity in both species, but browning still occurred in RC. Sulphite did not affect the polyphenol (PP) content in WC, rather suggesting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Higher N content could be achieved by adding a washing step for the acid-precipitated protein (P3) prior to resolubilization, as this would remove some of the co-precipitated compounds present. Several factors are known to have an impact on resolubilization of the white protein fraction, including pH, treatment temperature, use of enzymes, enzyme inhibitors, and adsorptive resins that influence the impact of phytochemicals on protein resolubilization [22,40,42,43]. The variation in protein resolubilization of the P3 fraction between biomass types might thus be the result of differences in phytochemicals binding to the proteins.…”
Section: Resolubilization Of the White Protein Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher N content could be achieved by adding a washing step for the acid-precipitated protein (P3) prior to resolubilization, as this would remove some of the co-precipitated compounds present. Several factors are known to have an impact on resolubilization of the white protein fraction, including pH, treatment temperature, use of enzymes, enzyme inhibitors, and adsorptive resins that influence the impact of phytochemicals on protein resolubilization [22,40,42,43]. The variation in protein resolubilization of the P3 fraction between biomass types might thus be the result of differences in phytochemicals binding to the proteins.…”
Section: Resolubilization Of the White Protein Fractionmentioning
confidence: 99%
“…Most published studies on protein fractionation from green biomass for food applications have applied a relatively gentle extraction process, to maintain the desirable functional properties of the proteins [18]. This process generally consists of three main steps (Figure 1): (i) pressing liquid from fresh or frozen green leaves to obtain a green juice (GJ); (ii) separating the green and white protein fractions by exploiting differences in thermal sensitivity of the proteins, to create white juice (WJ) and a green protein fraction [11,13,[18][19][20][21]; and (iii) concentrating the white protein fraction in the WJ further, by heating at 80 • C [19], acid precipitation at pH between 3.5 and 4.5 [13,16,[22][23][24], chromatography [20], or filtration [11,17]. Industrial-scale protein fractionation of green leaves for food would require a yearround process where a range of different biomass types are used in a similar methodological system.…”
Section: Introductionmentioning
confidence: 99%
“…This may further lead to the formation of cross-linked protein polymers (Rawel et al 2001). These phenol/quinone-protein bindings decrease the digestibility and solubility of the proteins (Rawel et al 2001;Bleakley and Hayes 2017;Wong and Cheung 2001;Amer et al 2020). Moreover, when phenolic compounds are oxidized to quinones, the quinones can polymerize and form brown pigments (Bittner 2006;Friedman 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The exact role of PPO in plants remains unresolved, but it has been suggested to be part of the defense against biotic stressors . Some of the polyphenols commonly present in plant material are chlorogenic acid and caffeic acid, and the quinone derivatives of these have been shown to react with amino acids in free form, in peptides and when present in proteins. The formed quinones are highly reactive electrophiles, which can nonenzymatically react with themselves to form brown polymeric pigments or with amino acids such as lysine, cysteine, methionine, and tryptophan in proteins. , The reaction between polyphenols and proteins in model systems changes the physicochemical properties of the protein including protein dimerization through cross-linking and reduced solubility and lowers the nutritional value of the protein in rats. , However, a recent study on alfalfa protein concentrates found that although sulfite increased the amounts of native RuBisCo subunits, sulfite addition reduced the protein solubility at neutral pH after acid precipitation …”
Section: Protein Qualitymentioning
confidence: 99%